Monitoring the Coefficient of Variation Using a Variable Sampling Interval EWMA Chart - Yeong, W.C.; Khoo, M.B.C.; Tham, L.K.; Teoh, W.L.; Rahim, M.A. (American Society for Quality, 2017)
In recent years, the coefficient of variation (CV) chart is receiving increasing attention in quality control. A number of studies demonstrated that adaptive charts could detect process shifts faster than traditional charts. This paper proposes an EWMA chart with variable sampling interval (VSI) to monitor the CV. Formulas for computing the performance measures of the VSI EWMA-γ2; chart are derived using Markov chain, where γ2 denotes the CV squared. Comparative studies show that the VSI EWMA-γ2 chart significantly outperforms other competing charts. An example using real manufacturing data shows that the VSI EWMA-γ2 chart performs well in applications.